The Biological Characteristic of Representatives of the Genus Hepatozoon (Apicomplexa, Adeleorina) in the Marsh Frog (Pelophylax ridibundus) Separate Populations of Zaporozhzhya Region - Korzh, A.P.; Zadorozhnyaya, V.Y. (Вестник зоологии, 2013)
In blood of frogs in two of seven studied biotopes the presence of the genus Hepatozoon representatives was revealed. Morphometric parametres allowed defining a specific accessory of the revealed haemoparasite Hepatozoon in a blood channel of village Malozaharino frogs which were closest to the species H. magna (Grassi et Feletti, 1891) Labbe, 1899.